Guidelines for Osteoprotection in Breast Cancer Patients on an Aromatase Inhibitor - Hadji, Peyman (S. Karger GmbH, 2010)
Postmenopausal women are at an increased risk of osteopenia and osteoporosis due to the physiologic loss of the bone protective effects of estrogen. Additionally, disease-related risk factors also contribute to the increased fracture risk. To further complicate matters, one of the most common and severe safety issues associated with cancer therapies for breast cancer patients is bone loss and the associated increased risk of fractures. These facts underscore the need to carefully monitor bone mineral density in patients with endocrine-responsive breast cancer, and to consider adjuvant therapy that may help manage and/or prevent bone loss and fracture. Aromatase inhibitors (AIs) are now in widespread clinical use for women with hormone receptor-positive breast cancer and have replaced tamoxifen as the gold standard of care. AIs target the estrogen biosynthetic pathway and deprive tumor cells of the growth-promoting effects of estrogen. These treatments provide significant benefit to patients in terms of improved disease-free and overall survival. Adversely, there is a concern of an increased risk of bone loss with prolonged therapy consequently leading to an increased fracture risk. This manuscript will review the recent literature pertaining to AI-associated bone loss and discuss suggested management and preventative approaches that may help patients remain on therapy to derive the most clinical benefits.